TINJAUAN HUKUM PERKAWINAN ISLAM TERHADAP PERKAWINAN KAFAAH SAYYID-SYARIFAH PADA KOMUNITAS ARAB TERNATE - Ismail, Nining Zahara; Abubakar, Fatum; Sanmas, Abu; Fadhly, Muhammad; Killian, Nursinita (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2024)
This research aims to find out what the kafa'ah concept of sayyid-syarifah marriage is and analyze this concept using Islamic Marriage Law. This research is a type of qualitative research. By using data collection techniques through observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and data verification. The results of the research show that the concept of kafa'ah applied by sayyid-syarifah in Ternate City is the concept of kafa'ah nasab. The goal is to ensure that their lineage is not interrupted. To achieve the concept of kafa'ah nasab, sayyid-syarifah carry out endogamous marriages, namely marriages carried out with members of the same group to achieve certain goals. Endogamous marriage is permitted in Islam, as long as it is not included in mawani' al-nikah. The conclusion obtained is that the sayyid-syarifah in Ternate City are strongly encouraged to maintain and carry out mutual marriages, especially the syarifah. Because they have a big responsibility for maintaining their lineage, if they marry someone who is not a sayyid then that lineage will be broken.